Application of Restorative Justice for Child Protection: Penerapan Restorative Justice Terhadap Perlindungan Anak - Hulu, Aluiziso (UPMI Proceeding Series, 2023)
The application of the Restorative Justice system to children who are in conflict with the law is an important alternative in considering children as perpetrators of violent crimes that result in physical and psychological violence. This type of research is research using a qualitative descriptive approach. Data collection in this study was carried out through a literature study, where the data obtained will be systematically arranged and analyzed using Restorative Justice. The restorative justice approach basically exists to reduce the number of inmates in correctional institutions. Therefore, as much as possible it is resolved peacefully (mediation) with the aim of restoring the situation to normal and restoring the pattern of good relations in society. In cases of sexual violence, the losses suffered by victims are not only physical and material, but also psychological and social. Can Restorative Justice protect victims and guarantee victims' rights, of course this is still a big question mark. Physical and material losses may recover in a short time, but psychologically it takes a very long time, even a lifetime. In addition, there is no security guarantee that the perpetrator will not make threats against the victim or even repeat his actions when the Restorative Justice process is complete.